Advanced non‐alcoholic fatty liver disease and adipose tissue fibrosis in patients with Alström syndrome. (10th June 2016) - Gathercole, Laura L.; Hazlehurst, Jonathan M.; Armstrong, Matthew J.; Crowley, Rachel; Boocock, Sarah; O'Reilly, Michael W.; Round, Maria; Brown, Rachel; Bolton, Shaun; Cramb, Robert; Newsome, Phillip N.; Semple, Robert K.; et al.
Abstract: Background and Aims: Alström syndrome (AS) is a recessive monogenic syndrome characterized by obesity, extreme insulin resistance and multi‐organ fibrosis. Despite phenotypically being high risk of non‐alcoholic fatty liver disease (NAFLD), there is a lack of data on the extent of fibrosis in the liver and its close links to adipose in patients with AS. Our aim was to characterize the hepatic and adipose phenotype in patients with AS. Methods: Observational cohort study with comprehensive assessment of metabolic liver phenotype including liver elastography (Fibroscan ® ), serum Enhanced Liver Fibrosis (ELF) Panel and liver histology. In addition, abdominal adipose histology and gene expression was assessed. We recruited 30 patients from the UK national AS clinic. A subset of six patients underwent adipose biopsies which was compared with control tissue from nine healthy participants. Results: Patients were overweight/obese (BMI 29.3 (25.95–34.05) kg/m 2 ). A total of 80% (24/30) were diabetic; 74% (20/27) had liver ultrasound scanning suggestive of NAFLD. As judged by the ELF panel, 96% (24/25) were categorized as having fibrosis and 10/21 (48%) had liver elastography consistent with advanced liver fibrosis/cirrhosis. In 7/8 selected cases, there was evidence of advanced NAFLD on liver histology. Adipose tissue histology showed marked fibrosis as well as disordered pro‐inflammatory and fibrotic gene expression profiles. Conclusions: NAFLD and adipose dysfunction are common in patients with AS. The severity of liver disease in our cohort supports the need for screening of liver fibrosis in AS.